Predicting Malaria Incidence in Northern and Northwestern, Pakistan - Muhammad IMRAN KHAN; Humera QURESHI; Henock AMBACHEW; Hai-Feng PAN; Dong-Qing YE (Tehran University of Medical Sciences, 2018)
Predicting Malaria Incidence in Northern and Northwestern, Pakistan